518 Phase 1B trial of monalizumab (NKG2A inhibitor) plus durvalumab: safety and efficacy in patients with metastatic ovarian, cervical, and microsatellite-stable endometrial cancers. (4th December 2020) - Banerjee, Susana; Oaknin, Ana; Sanchez-Simon, Inmaculada; Salgado, Alfonso Cortes; Patel, Sandip Pravin; Oza, Amit; Das, Mayukh; Kourtesis, Panagiotis; Ascierto, Maria Libera; Diamond, Jennifer R
Abstract : Introduction/Background: The immune checkpoints NKG2A and programmed cell death-1 (PD-1) are expressed on both tumour-infiltrating natural killer (NK) and CD8+ T cells in several cancer types, and are implicated in reducing antitumor immune response. To evaluate whether dual targeting of non-redundant checkpoint pathways (NKG2A/HLA-E and PD-1/PD-L1) may enhance antitumour immunity, the combination of monalizumab and durvalumab is being assessed in a Phase 1b expansion study in multiple solid tumours (NCT02671435 ). Here we report safety and efficacy results in patients with ovarian, cervical or microsatellite-stable (MSS) endometrial cancer. Methodology: Eligible patients had advanced recurrent or metastatic high-grade serous epithelial ovarian cancer or cervical cancer (patients in each cohort could have received up to 2 prior lines of systemic therapy) or MSS endometrial cancer (patients could have received up to 3 prior lines of systemic therapy), with Eastern Cooperative Oncology Group performance status 0–1. Patients received monalizumab 750 mg Q2W and durvalumab 1500 mg Q4W for up to 3 years until unacceptable toxicity or confirmed progression. The primary endpoint was safety and tolerability; secondary endpoints included antitumour activity. Results: Between March 2017 and March 2019, 40 patients with ovarian cancer (age range, 42–75 years), 16 patients with cervical cancer (age range, 32–79 years) and 40 patients with MSS endometrial cancer (age range, 45–79 years) were enrolled. Rates of treatment-related adverse events (AEs) were generally similar across cohorts (table 1 ). There were no grade 5 AEs and no events leading to discontinuation of monalizumab or durvalumab. Objective responses were seen only in ovarian cancer (table 2 ): among the 37 evaluable patients, 2 (5.4%) had confirmed partial responses and 10 (27.0%) had stable disease (SD) including 6 (16.2%) with disease control at 24 weeks (DCR24). Median progression-free survival (mPFS) was 1.8 months and median overall survival (mOS) was 16.7 months. Six (37.5%) of the 16 evaluable patients with cervical cancer had SD; mPFS was 2.0 months and mOS was 8.6 months. Fifteen (38.5%) of the 39 evaluable patients with MSS endometrial cancer had SD, including 5 (12.8%) with DCR24; mPFS was 1.8 months and mOS was 10.7 months. Conclusion: Monalizumab plus durvalumab treatment had manageable safety in all cohorts. Modest clinical activity was demonstrated in recurrent ovarian cancer, whereas activity in cervical and MSS endometrial cancers was minimal. Further understanding of dual immune-checkpoint targeting is required. Disclosures: Susana Banerjee has received institution research grants from AstraZeneca, Tesaro, and GlaxoSmithKline, and honoraria for advisory boards/lectures from AstraZeneca, Amgen, Clovis, Genmab, GlaxoSmithKline, Immunogen, Mersana, Merck Serono, Merck Sharp & Dohme, Pfizer, Roche, Seattle Genetics, and Tesaro. Ana Oaknin has served on advisory boards for Clovis Oncology, AstraZeneca, Genmab/Seattle Genetics, ImmunoGen, PharmaMar, Roche, GSK/Tesaro, Merck/Merck Sharp & Dohme, Deciphera and Mersana; has received support for travel or accommodation from Clovis Oncology, AstraZeneca, PharmaMar, and Roche; and reports institutional research grant support from Clovis Oncology, AbbVie Deutschland, Ability Pharmaceuticals, Advaxis, Aeterna Zentaris, Amgen, Aprea Therapeutics, Eisai, ImmunoGen, Merck/Merck Sharp & Dohme, Millennium Pharmaceuticals, PharmaMar, Roche, and Tesaro. IS-S: No conflicts to disclose ACS: No conflicts to disclose Sandip Pravin Patel receives scientific advisory income from AstraZeneca, Bristol Myers Squibb, Eli Lilly, Illumina, Rakuten, Paradigm and Tempus, and research funding from Bristol Myers Squibb, Eli Lilly, Incyte, AstraZeneca, Merck, Pfizer, Roche/Genentech, Xcovery, Fate Therapeutics, Genocea and Iovance. AOz: No conflicts to disclose Mayukh Das is an employee of and stockholder in AstraZeneca. Panagiotis Kourtesis is an employee of and stockholder in AstraZeneca. Maria Libera Ascierto is an employee of and stockholder in AstraZeneca. Jennifer R. Diamond reports research funding from AstraZeneca, Immunomedics, OnKure, Bristol Myers Squibb, Merck, Deciphera, Bayer, Taiho and Takeda and consulting work for Immunomedics.